2007
DOI: 10.1016/j.psychres.2006.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders and suicidal ideation in patients with depressive disorder

Abstract: An intrinsic association between suicidal ideation and sleep disorders in patients with depressive disorder has been observed in recent studies. This study was conducted in order to examine the relationship between suicidal ideation and sleep disorders, such as insomnia and excessive sleepiness, in outpatients with major depressive disorder. Seventy patients with diagnoses of major depressive disorder were interviewed and assessed with the Sleep Habits Questionnaire and the Beck Scale for Suicidal Ideation (SS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
60
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(71 citation statements)
references
References 19 publications
(16 reference statements)
7
60
2
2
Order By: Relevance
“…The "suicidal ideators" had the worst rates for quality of sleep (PSQI), sleep alterations (PSQI), global score (PSQI), anxiety (BAI), and depression (BDI), which allows us to suggest a strong association between anxiety and depression and sleep. Several studies have identified important relationships between sleep disorders, depression, suicidal ideation, and suicide 10,11,12,13,14,15 . Bernert and Joiner 13 observed that higher depression levels largely explained the relationship between sleep disorders and suicide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The "suicidal ideators" had the worst rates for quality of sleep (PSQI), sleep alterations (PSQI), global score (PSQI), anxiety (BAI), and depression (BDI), which allows us to suggest a strong association between anxiety and depression and sleep. Several studies have identified important relationships between sleep disorders, depression, suicidal ideation, and suicide 10,11,12,13,14,15 . Bernert and Joiner 13 observed that higher depression levels largely explained the relationship between sleep disorders and suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results revealed that depression (measured by the BDI) and sleep quality (as measured by the PSQI) were good predictors of suicidality in epilepsy. Considering these data, and recognizing that mood disorders 7 and sleep 10,11,12,13,14 are important risk factors for suicidal ideation and behavior, we recommend that the study and monitoring of these changes should be prioritized in the treatment of epilepsy, especially in cases of pharmaco-resistant epilepsy and/or psychiatric comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This unequivocal result was striking, considering that no specific relation of EDS with suicidal ideation had been previously described. An explanation for this finding may be that patients with severe depressive disorder rank daytime sleepiness in line with other major depressive symptoms [25][26][27]. If these findings are confirmed in a larger sample size, EDS should, therefore, be considered in the assessment of suicidal risk in depression.…”
Section: Eds and Depressionmentioning
confidence: 99%
“…Cross-sectionally, insomnia has repeatedly been linked to greater levels of suicidal ideation (Ağargün et al, 1997a;Barraclough and Pallis, 1975) even after controlling for depressive symptoms (Bernert et al, 2005(Bernert et al, , 2009Chellappa and Araújo, 2007), and suicidal behavior (Goldstein et al, 2008;Sjöström et al, 2007). Longitudinal studies (though few) provide even more compelling evidence, indicating that insomnia emerges as a significant predictor of later suicidal ideation (McCall et al, 2010) and death by suicide (Fawcett et al, 1990;Fujino et al, 2005;Turvey et al, 2002).…”
Section: Past Research On Sleep Problems and Suicidalitymentioning
confidence: 99%